0648 Sleep Paralysis in College Students: Prevalence, Subjective Experiences, and Correlates. (12th April 2019) - Benham, Grant; Barajas, Chasity; Martinez, Gerardo E; Gonzalez, Marco
Abstract: Introduction: Prior research suggests that approximately 28% of college students have experienced sleep paralysis (SP), a prevalence rate that is considerably higher than in the general population. The current study examined the prevalence, subjective experiences, and correlates of SP in a sample of predominantly Hispanic college students. Methods: 416 undergraduates (mean age 20.3, 95% Hispanic, 76% female) completed an online survey that contained questions about SP and a number of standardized measures, including insomnia (ISI), sleep quality (PSQI), and stress (PSS and ICSRLE). Results: Lifetime prevalence of SP in our sample was 35%, with 20% of the sample having experienced SP during the preceding year and 7% during the preceding month. Those who had experienced SP reported significantly greater insomnia, poorer sleep quality, greater life-events stress, and higher self-perceived stress (one-tailed independent t-tests, all p < .05). 73% first experienced SP as a child (<18 yrs). 54% generally experienced SP lasting three or more minutes and these individuals scored significantly higher on all aforementioned measures than those with shorter SP durations. 46% were most likely to experience SP when waking up vs. 23% when falling asleep. 71% found the SP experience "very frightening" or "terrifying". We examined the prevalence and intensity of a number of SP symptoms. E.g., inability to move body was strongly experienced by 76%; inability to speak, 70%; hearing unclear speech, 26%; sensed presence, 44%; seeing something or someone in the room or doorway, 42%; feeling of being touched, 34%. 38% believed that a strong shock or "susto" can cause SP and 32% believed SP could be helped by prayer. Participants also provided qualitative reports of their experiences and understandings of sleep paralysis, such as "se te subio el muerto" (the dead got on top of you). Conclusion: Limited data on the experience of SP exists, particularly in Hispanic samples. We found that SP is related to standardized measures of stress and standardized measures of sleep. Additionally, our data provide an expanded perspective on the subjective experiences and beliefs surrounding SP. Support (If Any): N/A